Teaching Factory-Based Learning Majoring in Machining Engineering at Vocational High School - Budi Tri Cahyono; Relly Prihatin; Taufiq Subhanul Qodr; Hilmawan Wibawanto; Nidhoil Mohamed Ibrahim (Universitas Sebelas Maret, 2026)
This study aims to analyze the effectiveness of the Teaching Factory (TEFA)-based learning model in improving the competence of machining engineering students at a vocational high school. It focuses on identifying differences in learning outcomes between students taught using TEFA integrated with industry standards and those taught using conventional methods. This research is important to ensure curriculum alignment with industry needs and to enhance graduate competitiveness in the Industry 4.0 era. This study employed a quantitative, quasi-experimental design. The population consisted of grade XI machining engineering students at Vocational High School Warga Surakarta, selected using cluster random sampling into experimental and control groups. Data were analyzed using one-way ANOVA. The results showed a significant difference in student competence, with TEFA outperforming conventional methods. TEFA creates a more relevant learning environment, improves discipline, and enhances technical skills in machine operation. These findings indicate that TEFA is effective and should be fully integrated into vocational school curricula.